Developing Quran-Integrated E-Modules on Salt Hydrolysis: A Learning Cycle 8E Approach for 11th Grade of Senior High School Students - Rizki, Gibrina; Mawarnis, Elvy Rahmi; Herman, Mimi (Universitas Pendidikan Mandalika, 2024)
The low learning outcomes of students are caused by limited teaching materials and educators who tend to use the lecture method during learning. This research aims to develop an E-Modules Based on Learning Cycle 8E Integrated with Al-Quran verses on Salt Hydrolysis Material for 11th Grade of Senior High School (SMA/MA) that are valid and practical. This research uses the Research and Development research type with the 4-D development model (define, design, develop, and disseminate). lkpHowever, only the first three stages of the model were implemented in this research. The results showed that 1) e-modules based on Learning Cycle 8E integrated with Al-Quran verses on salt hydrolysis material 11th Grade SMA / MA met the criteria very valid with a percentage of the validity of e-modules based on Learning Cycle 8E is 89%, the validity of content feasibility on integration with Al-Qur'an verses obtained a percentage of 90.6%. 2) e-modules based on Learning Cycle 8E integrated with Al- Quran verses on salt hydrolysis material for 11th Grade SMA/MA have met the criteria of being very practical with the results of the student response questionnaire obtaining a percentage of 84% and educators obtaining a percentage of 93%.